Evaluation of Critical MMAW Welding Defects Using Computer Simulation in Industrial Manufacturing Systems - Sindhu Kumar; Rone; Manish Kumar (International Journal of Industrial and Product Design Engineering, 2025)
Manufacturing is one of the key sectors of any countries GDP and welding is one of the prime manufacturing processes of the manufacturing sector. Welding has several notable advantages over mechanical joining techniques, including higher structural integrity, design flexibility, and cost and weight lowers. Welded products/structures are subjected to serious issues of residual stresses and distortions. The performance and sturdiness of the welded structures are severely impacted by weld remaining strain and deformation. Welding distortions introduce sever problems in assembling of the welded structures and reduce its quality. In some cases the higher values of the distortions make the products useless in shape. Whereas, the residual stresses cause the premature failures of the structures during the service life. Hence there is a need for suitable a methodology to control/minimize the residual stresses and distortions. Accordingly, this study has proposed three distinct methods, namely pre- setting, restraining and auxiliary side heating to control distortion in butt welds of MMAW process. Similarly auxiliary side heating is also proposed to control the residual stresses. For pre-setting the workpieces with known magnitudes of angular distortion in the opposite direction, a linear regression model based on five independent process parameters/factors (current, welding speed, electrode diameter, number of passes and plate thickness) is developed to predict the magnitude of angular distortion. The efficiency of linear regression model is tested through confirmation tests and it is found that a variation of the predicted angular distortion is within 10%. Similar to the regression model, use of Finite Element Analysis (FEA) is made for predicting angular distortion and residual stresses.
Keywords: Finite element analysis; MMAW process; WRSD; shielded metal Arc welding; submerged Arc welding